Case Report of Diffuse Parenchymal Lung Disease with Non-Specific Interstitial Pneumonia Pattern and Good Response to Treatment - Biswas, Muhammad Asaduzzaman; Islam, Muhammad Nazrul; Walid, Khalifa Mahmud; Rassel, Zhilam Zia (Faridpur Medical College Journal, 2019)
The diffuse parenchymal lung diseases (DPLDs) are a heterogeneous group of conditions affecting the pulmonary parenchyma (interstitial) and/or alveolar lumen. IPF (Idiopathic Pulmonary Fibrosis) is a chronic interstitial pneumonia of unknown causes. It is commonest form of DPLD but its treatment response is very poor. On the other hand, NSIP (Non-Specific Interstitial Pneumonia) can still be a variant of DPLD with better treatment response and prognosis. Here we discussed a young female with NSIP with good response to steroid. Faridpur Med. Coll. J. Jul 2018;13(2): 101-103